Pemanfaatan Limbah Kulit Jeruk Manis (Citrus Sinensis) Sebagai Obat Nyamuk Liquid Elektrik Yang Aman dan Ramah Lingkungan Di Desa Borisallo Kec Parangloe Kabupaten Gowa - Nurgahayu Nurgahayu; Arman Arman; Linda Hardianti Saputri (Fakultas Teknik Universitas Cenderawasih, 2023)
DHF cases in Indonesia in 2014 showed that there were 10 provinces in Indonesia that had the highest dengue cases and one of them was South Sulawesi Province (7). Based on data from the South Sulawesi Provincial Health Service, there were 2,166 people suffering from dengue fever from January to May 2020. 19 of them died. And the most in Gowa Regency were 6 people. Borisallo Village, Parangloe District, is one of the villages supported by the Indonesian Muslim University. We chose this location as a service partner area because dengue cases in Gowa Regency, based on the 2019 South Sulawesi Provincial Health Service Profile, were the 2nd highest area with dengue cases after Pangkep Regency, namely 474 sufferers. Then in 2020 Gowa Regency was the area with the most dengue cases, namely 457 people. The aim of this service is to improve cadres' skills in making their own mosquito repellent from natural ingredients that are safe and environmentally friendly, increase cadres' knowledge about the dangers of chemical mosquito repellent, increase cadres' knowledge in making preventive efforts against diseases transmitted by mosquito vectors. The solutions offered include training in making electric liquid mosquito repellent from sweet orange peel, providing education regarding the dangers of chemical mosquito repellent for health, providing education on preventive efforts to prevent diseases transmitted by mosquito vectors.